Recent advances in novel materials and techniques for developing transparent wound dressings - Kuddushi, Muzammil; Shah, Aatif Ali; Ayranci, Cagri; Zhang, Xuehua (Journal of materials chemistry. B, Materials for biology and medicine, 2023)
Optically transparent wound dressings offer a range of potential applications in biomedical fields, as they allow for the monitoring of wound-healing progress without having to replace the dressing. These dressings must be impermeable to water and bacteria, yet permeable to moisture vapor and atmospheric gases in order to maintain a moist environment at the wound site. This review article provides a comprehensive overview of the types of wound dressings, novel wound-dressing materials, advanced fabrication techniques for transparent wound-dressing materials, and the key features and applications of transparent dressings for the healing process, as well as how they can improve healing outcomes. This review mainly focuses on presenting specifications of transparent polymeric wound-dressing materials, such as transparent electrospun nanofibers, transparent crosslinked hydrogels, and transparent composite films/membranes. Due to the advanced properties of electrospun nanofibers, such as large surface area, efficient incorporation of antibacterial molecules, a structure similar to the extracellular matrix, and high mechanical stability, they are often used in wound-dressing applications. We also highlight hydrogels or films for wound-healing applications, and their promotion of the healing process, provision of a moist environment and pain relief through cooling and high-water content, excellent biocompatibility, and bio-biodegradability. But as hydrogels or films fabricated with a single component have low mechanical strength and stability, recent trends have offered composite or hybrid materials to achieve typical wound-dressing requirements. Advanced wound dressings with transparency, high mechanical stability, and antimicrobial functionality are becoming a popular research avenue in the wound-dressing research field. Finally, the developmental prospects of new transparent wound-dressing materials for future research are presented. This review article provides an overview of types of wound dressings, wound-dressing materials, advanced fabrication techniques, and key features and applications of transparent dressings for the healing process, as well as how they can improve healing outcomes.